Teori Transformatif Generatif Noam Chomsky (Study Atas Hadist Nabi Tentang Istiqamah) - Kholil, Mohammad Farhan; Ivani, Berlian; Afifah, Syifa Nur (CV. Eduartpia Publisher, 2025)
One of the sources of Islamic teachings is the hadith, which is the revelation or words conveyed by the Prophet Muhammad to his companions. Because the number of companions is large and each has a different level of understanding and capacity, it is not uncommon for the narrated hadith to have varying redactions, although the meaning remains similar. These editorial variations may affect the way the message is conveyed, but the essence remains consistent. This study aims to analyze the Prophet Muhammad's hadith about istiqamah using the Generative Transformation theory developed by Noam Chomsky. In this study, the two traditions that become the object of study are the traditions narrated by Imam Al-Darimi and Imam Ibn Majah. These two traditions will be analyzed through a descriptive qualitative text analysis approach, focusing on identifying the surface structure and deep structure of the two traditions. This analysis is expected to provide a deeper understanding of the differences and similarities that exist in the redaction of the hadith, as well as reveal the meaning contained therein. Thus, this study aims not only to understand the linguistic aspects of the traditions, but also to explore the messages contained in Islamic teachings, especially related to the concept of istiqamah